Informação, redes sociais e a construção de políticas públicas para o meio ambiente em Minas Gerais: A (re) configuração discursiva da Meta 2010 - Carolina de Souza Scott Mairinque (2010)
This essay depicts an analysis of the speech reconfiguration process in the construction of public policies regarding the environment. Using the Meta 2010 as an empiric scenario, the objective of this dissertation is to study the connection of the consolidation of these policies with social mobilization and access to information and communication, as well as the way the players involved in the process of a public policy construction organize themselves from their discourse's perspective, with emphasis, in such organization, on the relation between discourse, power and collective image. Considered a model of initiative in forming public policy, the Meta 2010 is a civil society proposal represented by Manuelzão, an extension project of the Federal University of Minas Gerais (Universidade Federal de Minas Gerais). The Meta 2010 was able to transform the proposal of revitalizing the hydrographical basin of Rio das Velhas into Minas Gerais state's public policy. To identify the discursive structure of Meta 2010, the analysis of a social network and the discourse analysis were used as methodological tools. The social network analysis contributed to identify the discursive centers of the political network built to manage Meta 2010 and the discourse analysis showed the way that these centralities structured their discourses on themselves. The present study concluded that, throughout its seven years of existence, Meta 2010 has suffered several discourse reconfigurations by the discursive communities of the identified centralities. The analysis showed the discursive process of transformation through which Meta 2010 moved on from a civil society proposal to a public policy of the state of Minas Gerais and became a new goal, called Meta 2014. Evidencing this transformation process, the study showed the points of contact and the distance between the discourses of the centralities, which were capable of suggesting discursive traces that distinguished them.